Control of Guest Inclusion and Chiral Recognition Ability of 6‐O‐Modified β‐Cyclodextrins in Organic Solvents by Aromatic Substituents at the 2‐O Position. Issue 8 (28th August 2020) - Kalaw, Justine M.; Yamamoto, Ryusuke; Kogame‐Asahara, Chizuru; Shigemitsu, Hajime; Kida, Toshiyuki
Abstract: The host‐guest chemistry and applications of cyclodextrins in aqueous media is well established. However, a comprehensive study in organic solvents is lacking. Here, we report the design and synthesis of 6‐ O ‐ tert ‐butyldimethylsilylated β‐cyclodextrin (TBDMS‐β‐CD) bearing various aromatic substitutions at the 2‐ O position and their inclusion complex formation with aromatic guests in nonpolar organic solvents. Compared to the parent TBDMS‐β‐CD, these derivatives exhibit at least a 10‐fold increase in inclusion ability toward pyrene through cooperative guest binding with the CD cavity and the aromatic substituents at the 2‐ O position. The type of the aromatic substituent largely affects the chiral recognition ability of TBDMS‐β‐CD toward 1‐(1‐naphthyl)ethylamine in cyclohexane. A TBDMS‐β‐CD derivative with a p ‐tolyl substituent has a remarkable chiral selectivity for the ( S )‐1‐(1‐naphthyl)ethylamine over the corresponding ( R )‐isomer ( KS /KR =4.1±0.5), whereas a TBDMS‐β‐CD derivative with a 2‐picolyl substituent shows the inverse chiral selectivity ( KR /KS =8.7±0.6). Abstract : Inclusion control : 6‐ O ‐ tert ‐Butyldimethylsilylated β‐cyclodextrin (TBDMS‐β‐CD) bearing various aromatic substitutions at the 2‐ O position were synthesized. These hosts exhibited large increases in the association constants with pyrene in nonpolar solvents compared to the bare TBDMS‐β‐CD. The type of aromatic substituent largely affected the chiral recognition ability of TBDMS‐β‐CD toward 1‐(1‐naphthyl)ethylamine in cyclohexane.